Climate change and Indigenous mental health in the Circumpolar North: A systematic review to inform clinical practice. (June 2022) - Lebel, Laurence; Paquin, Vincent; Kenny, Tiff-Annie; Fletcher, Christopher; Nadeau, Lucie; Chachamovich, Eduardo; Lemire, Mélanie
Climate change is disproportionally impacting the Circumpolar North, with particular impacts among Indigenous populations. Environmental changes are felt in many aspects of daily life of Northern communities, including both physical and mental health. Thus, health institutions from around the Arctic must meet emerging needs, while the phenomenon remains marginal to their southern counterparts. In this systematic review, we aimed to review current scientific knowledge on the mental health impacts of climate change in Indigenous Peoples across the Circumpolar North. Seven databases were searched. Original peer-reviewed research articles were included if they addressed links between climate change and mental health in Arctic or Subarctic Indigenous Populations. After extraction, data were synthesized using thematic analysis. Of the 26 articles that met inclusion criteria, 16 focused on Canadian Inuit communities and 21 were exclusively qualitative. Being on the land was identified as a central determinant of wellbeing. Immediate impacts of climate change on mental health were felt through restricted mobility and disrupted livelihoods. Effects on mental health were further felt through changes in culture and identity, food insecurity, interpersonal stress and conflicts, and housing problems. Various ways in how communities and individuals are coping with these effects were reported. Understanding climate-related pathways of mental health risks in the Arctic is crucial to better identify vulnerable groups and to foster resilience. Clinicians can play a role in recognizing and providing support for patients affected by these disruptions. Policies sensitive to the climate–mental health relationship must be advocated for.